Latin and Fundamentals of Medical Terminology : Set Tasks and Module Tasks for the І st year English-Speaking Students of the Medical Faculties (module I, II) - Тітієвська, Тетяна Василівна; Гордієнко, Олена В'ячеславівна; Куліченко, Алла Костянтинівна; Пашко, Олексій Єфремович; Titiyevska, T.; Gordiyenko, O.; Kulichenko, A.; Pashko, O. (Zaporizhzhia state medical university, 2016)
Set tasks and module tasks (module I, II) are made up for the І st year English-speaking students of the medical faculties. The aim is to check the knowledge and skills acquired by students during the course ‘Latin and Fundamentals of Medical Terminology’.
Латинська мова та основи медичної термінології. (Модуль 1, 2). Зб. контрольних завдань та типових задач для студ. – іноземних громадян І курсу мед. ф-тів